2021
DOI: 10.7577/rerm.4215
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Posthuman Conceptions of Change in Empirical Educational Research

Abstract: In this special issue of Reconceptualizing Educational Research Methodology the focus is on posthuman conceptions of change in empirical educational research. In the six included papers, the authors address and challenge different aspects of change in different educational settings – ranging from preschools, to universities and public pedagogies. Through activating posthuman perspectives, the papers invite the reader to a wide range of understandings of the concept of change. A conclusion drawn from the papers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The iterative teaching cycle is often illustrated as a circle or a spiral, emphasizing its continuous nature. This can be understood in line with posthuman onto-epistemologies where change, learning, and transformation are continuous and never-ending (Bodén et al, 2021). Education can with a posthuman and relational approach be understood as impermanent…”
Section: Iteration and Continuous Movementmentioning
confidence: 97%
“…The iterative teaching cycle is often illustrated as a circle or a spiral, emphasizing its continuous nature. This can be understood in line with posthuman onto-epistemologies where change, learning, and transformation are continuous and never-ending (Bodén et al, 2021). Education can with a posthuman and relational approach be understood as impermanent…”
Section: Iteration and Continuous Movementmentioning
confidence: 97%
“…P. Østern, 2019). Since educational practices always imply a certain form, which can be understood as a design, composition, or choreography, we recognize that the forms of teaching -specifically the "how" of teaching -are never neutral, irrelevant, or innocent (Bodén et al, 2021;Ulmer et al, 2020). For example, the challenging of the boundaries between human/nonhuman and matter/discourse extends notions of political agency (Zembylas, 2017), and therefore, thinking with post-approaches to education and the arts recognizes learning and teaching as political and ethical endeavors.…”
Section: Post-approaches To Education and The Artsmentioning
confidence: 99%
“…Change is central in education, and education is often connected to transformational processes for an individual or a group, loading the objects of change with new, more, and better abilities (Bodén et al, 2021). Therefore, change often has positive connotations and is seen as something desirable.…”
Section: Rethinking Changementioning
confidence: 99%
“…In general, TPA was not designed to say something about what constrains educational situations, but instead, in particular cases, to offer understanding by holding on to and unwinding from the practice (Kemmis et al, 2014a). Bodén et al (2021) remind us that "change is not something out there to be found, but an emergent phenomenon that unfolds as we explore it" (p. 7, italics in original).…”
Section: Rethinking Changementioning
confidence: 99%